A Différant Kind of Preaching: Derrida and the Deconstruction of Contemporary Homiletics - Jacob D. Myers (Religions, 2024)
Homiletics manifests as a technē that commends certain kinds of preaching over others. As such, homiletics structures debate unaware of the philosophical assumptions operative within it. This paper challenges the logocentrism of contemporary homiletical theories in light of Jacques Derrida’s deconstructive analytic. I take as my privileged conversation partner Fred Craddock, the much-lauded king of the New Homiletic. I argue that in commending inductive over deductive logic, Craddock merely inverts the logical movement of preaching, thereby reinscribing logocentrism. Utilizing Derrida’s neologism différance, I press homiletics toward what I am labeling conductive preaching, which reframes homiletical theory beyond the epistemological biases that condition it.